Michael D. Shaw conducting urine analysis at St. Francis Hospital toxicology laboratory - Perkin-Elmer Corporation (1970)
General view of medical technician Michael D. Shaw using a Perkin-Elmer Model 930 Gas Chromatograph to analyze a urine sample in the toxicology laboratory at St. Francis Hospital in Hartford, Connecticut. Per notations accompanying the photograph, Shaw is seen pinpointing a peak on the gas chromatograph's recording graph in order to determine which drug an apparent overdose victim had taken and develop a corresponding course of treatment.
Keywords: Urine--Analysis; Employees; Perkin-Elmer Corporation; Life sciences; Hospitals; Scientific apparatus and instruments; Corporations; Gas chromatography; Laboratories; African Americans; Shaw, Michael D.